(untitled) (Tempo e Argumento, 2021)
The worldwide expansion of the commercial cinema theater between 1908 and 1914 was remarkable, and undeniable. In this paper, we seek to demonstrate that this expansion, or industrialization of cinema, developed in business logic that sought to explore as much as possible the reproducibility of the film and the multiplication of the number of spectators. Then came the first idea of the modern public. The formation of this public also went through the naturalization of the mode of representation of classical cinema, with its themes and formats that instituted passivity in individuals before the films. However, the position of the early-twentieth-century French working class movement vis-à-vis the cinematographer demonstrates that the creation of this mode of representation was not passively felt. The social coexistence of the workers in the first years of cinema´s existence presented another form of relationship with the moving picture, different from the commercial one, pointing in the category of “public” a scale of analysis in contemporary history alternative to the consecrated notions of “mass” or “spectator”.